The BBI Combinatory Dictionary of English: A Guide to Word Combinations. Compiled by Morton Benson, Evelyn Benson and Robert Ilson. John Benjamins Publishing Company/Munksgaards Ordbøger, Amsterdam/Philadelphia 1986 - Poulsen, Sonja (HERMES - Journal of Language and Communication in Business, 1991)
No abstract.